Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0283
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Visible Spectra and Photoacidity of Phenols, Naphthols and Pyrenols

Abstract: Introduction The Thermodynamic Aspects of Photoacidity On the Origin of Photoacidity The Electronic Structure of Photoacids Free‐Energy Correlations Between Photoacidity and Reactivity Concluding Remarks: Evaluation of our Current Understanding of the Photoacidity of Hydroxyarenes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…For this purpose, we selected 2 oxygen bases with structures and pK a s relevant to biological systems: the HPTS base 8hydroxy-1,3,6-trisulfonate anion, and the 1N4S base 1-naphthol-4-sulfonate anion. The pK o a s (I = 0) of these 2 bases' conjugate Brønsted acids (H + Bs) are 7.95 and 8.2, respectively (54,55). HPTS and 1N4S have basicity similar to that of many important physiological bases such the amine groups in small peptides, the hydroxyl group in tyrosine, and the imine group in histidine, whose conjugate acids' pK o a s all fall in the range of 8 ± 2 (56).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we selected 2 oxygen bases with structures and pK a s relevant to biological systems: the HPTS base 8hydroxy-1,3,6-trisulfonate anion, and the 1N4S base 1-naphthol-4-sulfonate anion. The pK o a s (I = 0) of these 2 bases' conjugate Brønsted acids (H + Bs) are 7.95 and 8.2, respectively (54,55). HPTS and 1N4S have basicity similar to that of many important physiological bases such the amine groups in small peptides, the hydroxyl group in tyrosine, and the imine group in histidine, whose conjugate acids' pK o a s all fall in the range of 8 ± 2 (56).…”
Section: Resultsmentioning
confidence: 99%
“…Both values are in the typical p K a -range of pyrenol-derived photoacids. 31 After polymerization the acidity of the 1-pyrenols was found to increase slightly yielding p K a values ranging from 8.7 for P[(OEG 9 MA) 0.88 - co -HPSAPMA 0.12 ] to 9.8 in P[(OEG 3 MA) 0.86 - co -HPSAPMA 0.14 ] (see Table 2 for more details). In case of the OEG 3 MA-based copolymers, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 The most prominent photoacids known are hydroxyarenes such as phenols, naphthols, or pyrenols. [28][29][30][31] In our previous work we successfully demonstrated that the UV light initiated ESPT in micelles formed of 1-naphthol-carrying copolymers with photoacid moieties in the micellar core contributes to the release of the encapsulated model compound Nile red. 21,22 However, the necessity of UV light to release the drug from the nanoparticles reduces the potential of these polymers in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Table S6). This is within expectations, given that the Förster’s method provides a rough estimate of photoacidity because of the assumption that the entropy change is same in the ground and excited states and also because of errors associated in determining the 0–0 transition energies of the conjugate acid and base forms …”
Section: Resultsmentioning
confidence: 99%